2020
DOI: 10.4102/sajip.v46i0.1781
|View full text |Cite
|
Sign up to set email alerts
|

Impact of psychological capital on employee engagement, job satisfaction and employee performance in the manufacturing sector in Zimbabwe

Abstract: Orientation: Human capital lies at the heart and centre of any organisation’s success. It is for this reason that entrepreneurial envisioned corporations embrace the role of psychological capital in order to optimise their employees’ competences and potential.Research purpose: The study underscores the role that psychological capital plays on employee engagement, job satisfaction and employees’ performance in the manufacturing sector of a developing country context.Motivation for the study: The study was motiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 30 publications
3
37
0
7
Order By: Relevance
“…The findings of Sekhar, Patwardhan & Vyas (2017) that individuals who feel engaged with their work and have a higher sense and involvement in activities in their organization will produce good job performance (Ngwenya, & Pelser, 2020). This is in line with existing findings that indicate employee engagement, directly and indirectly, affects individual performance (Azizah & Gustomo, 2015).…”
Section: Resultssupporting
confidence: 86%
“…The findings of Sekhar, Patwardhan & Vyas (2017) that individuals who feel engaged with their work and have a higher sense and involvement in activities in their organization will produce good job performance (Ngwenya, & Pelser, 2020). This is in line with existing findings that indicate employee engagement, directly and indirectly, affects individual performance (Azizah & Gustomo, 2015).…”
Section: Resultssupporting
confidence: 86%
“…The study on employee engagement has emerged reasonably in the recent literature. A recent study by Ngwenya and Pelser (2020) in the manufacturing sector in Zimbabwe has shown that employee engagement has significantly influenced employee performance and job satisfaction positively influenced employee engagement. Another empirical study on employee engagement and job satisfaction in China indicated that workplace has a large influence on employee engagement and job satisfaction (Rashidin, Javed & Liu, 2020).…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 99%
“…Hence it is vital to make sure that employees have the skills that meet organizational needs. Furthermore, human capital leads to organizational success and organizations need to maximize human resources competencies strategically to boost employees" performance (Ngwenya & Pelser, 2020). According to Zahari et al, (2020) the successfulness of an organisation has been associated to attain job satisfaction at a greater level.…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 99%
“…In contrast, through experiencing positive emotions, employees are engaged in their work which in turn creates a positive impact on their performance [11]. These individuals involve themselves in activities and attain high job performance, indicating individual performance is directly and indirectly linked with employee engagement [12] which is shaped through organisational behaviour. The level of stress encountered within the organisation affects employee performance levels.…”
Section: Motivationmentioning
confidence: 99%